A girls' eye view of aggressive adolescent female behaviour : a thesis submitted in partial fulfilment of the requirements for the degree of Doctor of Education, Massey University - Arnott, Rosemary M (Massey University, 2010)
This thesis challenges media claims that adolescent girls in New Zealand are becoming more aggressive and are therefore behaving like boys. Most early studies of aggression ignored girls entirely or presented them as a subset of boys. Although later studies did address issues around girls’ aggressive behaviour, these were largely focused on adults’ views of girls’ relational or social aggression. This doctoral study therefore used a small case study to explore adolescent aggression from the perspective of six adolescent girls whose behaviour had been described by their schools as aggressive. The girls’ accounts of their experiences and beliefs about gender-specific aggression were gathered via a series of individual conversational interviews, and initially analysed through the theoretical perspective of role theory and psychological perspectives on aggression. However, as the study progressed, the limitations of that approach became apparent and the girls’ transcripts were revisited via the lens of poststructural theory, using the tools of discourse analysis. The study found that these girls’ behaviours and beliefs did not fit the description of severe adolescent female aggression as described in the literature. Nor did the risk factors most commonly associated with aggression at adolescence appear to have affected them. Conversely, it would appear that their physicality influenced how they positioned themselves and how others positioned them; as “sporty girls”, “tomboys”, “loving daughters and siblings”, or as “righteous aggressors”. Their behaviours frequently challenged the dominant discourse of conventional schoolgirls. None of them thought that girls were becoming more aggressive and all stated that girls could behave how they wanted without being labelled de facto boys. This study was limited in terms of the number of participants and the range of cultures represented, therefore no generalisations can be drawn from it. Nevertheless, it does have some important implications for policy makers and practitioners: particularly that interactions of culture, class and gender impact on the way that individuals constitute themselves and others. Interpretations of behaviour are determined by the discursive context and the experiences and belief systems of both “actor” and “audience”.
Keywords: Adolescent girls; Aggression; Aggressive behaviour; New Zealand; Adolescents; Fields of Research::330000 Education::330100 Education Studies::330103 Sociology of education